Pollution release type marine antifouling paint with soft and hard segment collaborative topological structure and preparation method of pollution release type marine antifouling paint
A soft-hard segment synergistic topological structure in marine antifouling coatings addresses adhesion issues by enhancing bonding with substrates while maintaining low surface energy for effective antifouling performance.
Patent Information
- Application Number
- CN202411355985.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing organic silicon marine antifouling coatings suffer from poor adhesion to polar metal substrates, leading to peeling and limited large-scale application due to their low surface energy characteristics.
A fouling-release marine antifouling coating with a soft-hard segment synergistic topological structure is developed, incorporating hydrophobic methylsiloxane as the main chain and hard segment molecular segments at both ends, synthesized through an in-situ ester cross-linking reaction to enhance bonding with substrates while maintaining low surface energy for antifouling.
The coating achieves strong bonding to substrates, preventing peeling and maintaining excellent antifouling properties by ensuring cohesion and adhesion, suitable for long-term immersion in seawater environments.
Smart Images

Figure BDA0005063612560000011 
Figure BDA0005063612560000031 
Figure BDA0005063612560000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of marine antifouling coating technology and underwater coating protection technology, and relates to a fouling-releasing marine antifouling coating with a soft-hard segment coordinated topological structure and a preparation method thereof. Background Art
[0002] Marine biofouling is a major problem faced by countries around the world in developing their marine industries, and applying antifouling paint is the most effective and convenient way to solve this problem.
[0003] Organic silicon environmentally friendly marine antifouling coatings belong to fouling-releasing marine antifouling coatings. With the help of the low surface energy and unique non-polarity of organic silicon film-forming coatings, the adhesion of fouling organisms on the coating surface is effectively inhibited. In addition, the elastic modulus of organic silicon coatings is low, and the adhered organisms can be peeled off from the coating surface by a low-energy stripping method. For ships sailing on the ocean, with the help of the water flow scouring brought about by the relative movement with seawater, the loosely adhered fouling organisms can be easily removed. At present, the relevant coatings have great development and application prospects. However, it is precisely because of the low surface energy characteristics of organic silicon resins that the cured organic silicon coatings are often difficult to adhere to polar metal substrates. And this low adhesion to the metal substrate or the corresponding intermediate connecting paint will cause the corresponding coating to peel off and fall off over a large area during use, especially during long-term service in (sea) water. The easy-to-fall-off problem caused by this low adhesion has seriously limited the large-scale application of relevant organic silicon marine antifouling coatings. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a fouling-release marine antifouling coating with a soft-hard segment synergistic topological structure and a preparation method thereof in order to address the defects of polysiloxane fouling-release marine antifouling coatings such as poor adhesion to substrates and easy falling off.
[0005] Technical solution: The fouling-releasing marine antifouling coating of the soft-hard segment coordinated topological structure of the present invention comprises, by weight:
[0006]
[0007] The structure of the soft and hard segment cooperatively modified polysiloxane polymer is that the main chain is hydrophobic methylsiloxane, and the two ends are hard segment molecular segments from anionic monomers and hydrophilic amide monomers.
[0008] Furthermore, the soft and hard segment synergistically modified polysiloxane polymer is prepared by the following steps:
[0009] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, an anionic monomer, a hydrophilic amide monomer, a carboxyl polysiloxane and a second solvent are added in sequence, and then the pH is adjusted to be greater than 10 by a mixed solution of sodium hydroxide (1 g) / ethanol (10 g), and the reaction is stirred at 20 to 100 rpm at 40 to 50° C. for 10 to 20 hours;
[0010] (2) The precipitated product after the reaction is filtered, washed with deionized water for at least 3 times, and then dried in a vacuum device for 24 hours to obtain a soft and hard segment synergistically modified polysiloxane polymer.
[0011] Furthermore, the weight ratio of the anionic monomer, the hydrophilic amide monomer, the carboxyl polysiloxane and the solvent is (3-8): (5-10): (50-80): (100-150).
[0012] Furthermore, the anionic monomer is selected from one of sodium 2-carboxyethyl acrylate, sodium acrylate, sodium indoleacrylate, and sodium alginate.
[0013] Furthermore, the hydrophilic amide monomer is selected from one of N-(2-hydroxyethyl) acrylamide, methacrylamide and dimethylaminopropyl acrylamide.
[0014] Furthermore, the carboxyl polysiloxane is selected from dicarboxyl-terminated polysiloxane, and its viscosity at room temperature is 2000-5000 mPa·s.
[0015] Furthermore, the second solvent is selected from one of ethanol, acetone and toluene.
[0016] Furthermore, the auxiliary agent is selected from at least one of a wetting and dispersing agent, a defoaming agent, and a leveling agent.
[0017] Specifically, the wetting and dispersing agent is selected from BYK116, BYK169 of BYK Company, and 901, 903 of Deqian Company.
[0018] Specifically, the defoaming agent is selected from BYK065, BYK066N of BYK Company, and EFKA2020 of Efka of the Netherlands.
[0019] Specifically, the leveling agent is selected from one of German BYK308, BYK310 and BYK373.
[0020] Furthermore, the color filler is selected from but not limited to one of calcium carbonate, ferric oxide, titanium dioxide, barium sulfate, kaolin and zinc oxide.
[0021] Furthermore, the first solvent is selected from one of methanol, xylene and acetone.
[0022] Furthermore, the present invention provides a method for preparing the above-mentioned fouling-release marine antifouling coating with a soft and hard segment coordinated topological structure, comprising the following steps: (1) in a reaction device protected by nitrogen and connected to a stirring and reflux device, an anionic monomer, a hydrophilic amide monomer, a carboxyl polysiloxane and a second solvent are added in sequence, and then the pH is adjusted to greater than 10 by a sodium hydroxide / ethanol mixed solution, and the reaction is stirred at 20 to 100 rpm at 40 to 50° C. for 10 to 20 hours;
[0023] (2) filtering the precipitated product after the reaction, washing it with deionized water for at least three times, and then drying it in a vacuum device to obtain a soft and hard segment synergistically modified polysiloxane polymer;
[0024] (3) Add the soft and hard segment synergistic modified polysiloxane polymer and the additive obtained in step 2 to the dispersing and stirring equipment in sequence, stir and disperse, then add the pigment, filler and the first solvent to the dispersing and stirring equipment and continue to stir and disperse, so as to obtain the fouling-release marine antifouling coating with a soft and hard segment synergistic topological structure, and then seal and store.
[0025] Furthermore, the present invention provides a method for preparing a coating using the above-mentioned coating, wherein the coating is applied by spraying, rolling or brushing, and cured for at least 48 hours to prepare a coating with a film thickness of 150 to 250 um.
[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) Through an in-situ ester cross-linking reaction, the hard segment molecular chain segments (derived from anionic monomers and hydrophilic amide monomers) are introduced into the soft segment polysiloxane molecular structure (derived from carboxyl polysiloxane). This synergy between the soft and hard segments can effectively improve the topological structure entropy of the synthetic polymer, thereby achieving coordination between the cohesion and adhesion of the synthetic polymer, and achieving excellent bonding effect of the modified polymer;
[0027] (2) The soft and hard segments of the modified polysiloxane polymer as the main film-forming material still have a hydrophobic methylsiloxane structure as the main chain of the molecule. At the same time, the hard segments introduced are at both ends of the polymer molecular structure. Therefore, the cured coating still has excellent hydrophobicity, thereby maintaining low surface energy characteristics during subsequent service and having excellent antifouling effect;
[0028] (3) The present invention synthesizes a modified polysiloxane polymer with excellent bonding effect through a simple in-situ ester exchange reaction, and the hard segment molecular structure is located at both ends of the polymer molecular chain. Therefore, after curing and forming a film, the hard segment structure with excellent bonding effect is enriched in the coating and substrate area through the movement of the molecular chain segments, and the coating has strong bonding properties. The soft segment structure with low surface energy is located on the surface of the coating, ensuring the excellent antifouling effect of the coating. Through the molecular migration movement during the curing process, the coating is firmly bonded and has antifouling properties;
[0029] (4) The coating of the present invention is used for antifouling of marine facilities, and is particularly suitable for various marine facilities that are immersed in seawater environment for a long time. It has excellent antifouling properties and is not easy to fall off. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0031] The coating of the present invention effectively improves the topological structure entropy of the methylsiloxane polymer by grafting a hard segment molecular structure with polar and anionic properties on the methylsiloxane of the soft segment through the synergistic effect of the soft and hard segments, thereby achieving coordination between the cohesion and adhesion of the modified polymer and achieving excellent bonding effect of the modified polymer. The hard segment molecular structure is located at both ends of the modified polymer molecular chain, thereby avoiding the destruction of the low surface energy of the cured coating caused by chemical modification, so that the cured coating still has excellent antifouling effect.
[0032] The soft and hard segment synergistic modified polysiloxane polymers 1-3 involved in Examples 1-5 were prepared by the following Synthesis Examples 1-3, respectively. The raw materials used in Synthesis Examples 1-3 and Examples 1-5 are shown in Table 1. The specific implementation is not limited to the raw materials in Table 1, and the corresponding products can be selected according to the above. The other raw materials used in the examples are all commercially available chemical reagents.
[0033] Table 1
[0034]
[0035]
[0036] Synthesis example 1
[0037] The weight ratio of the anionic monomer, the hydrophilic amide monomer, the carboxyl polysiloxane and the second solvent is 6:5:70:100. The specific preparation steps are as follows:
[0038] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, anionic monomer 1-1, hydrophilic amide monomer 2-2, carboxyl polysiloxane 3-1 and second solvent 4-1 are added in sequence, and then the pH is adjusted to greater than 10 with a mixed solution of sodium hydroxide (1 g) / ethanol (10 g), and the reaction is stirred at 50 rpm at 40° C. for 16 hours;
[0039] (2) The precipitated product after the reaction was filtered, washed with deionized water for at least 3 times, and then dried in a vacuum device for 24 hours to prepare a soft and hard segment synergistically modified polysiloxane polymer 1.
[0040] Synthesis example 2
[0041] The weight ratio of the anionic monomer, the hydrophilic amide monomer, the carboxyl polysiloxane and the second solvent is 3:10:50:120. The specific preparation steps are as follows:
[0042] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, anionic monomer 1-2, hydrophilic amide monomer 2-1, carboxyl polysiloxane 3-1 and second solvent 4-2 are added in sequence, and then the pH is adjusted to greater than 10 with a mixed solution of sodium hydroxide (1 g) / ethanol (10 g), and the reaction is stirred at 20 rpm at 45° C. for 10 hours;
[0043] (2) The precipitated product after the reaction was filtered, washed with deionized water for at least 3 times, and then dried in a vacuum device for 24 hours to prepare the soft and hard segment synergistically modified polysiloxane polymer 2.
[0044] Synthesis example 3
[0045] The weight ratio of the anionic monomer, the hydrophilic amide monomer, the carboxyl polysiloxane and the second solvent is 8:8:80:150. The specific preparation steps are as follows:
[0046] (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, anionic monomers 1-3, hydrophilic amide monomers 2-3, carboxyl polysiloxane 3-2 and a second solvent 4-2 are added in sequence, and then the pH is adjusted to greater than 10 with a sodium hydroxide (1 g) / ethanol (10 g) mixed solution, and the reaction is stirred at 20 rpm at 45° C. for 10 hours;
[0047] (2) The precipitated product after the reaction was filtered, washed with deionized water for at least 3 times, and then dried in a vacuum device for 24 hours to prepare the soft and hard segment synergistically modified polysiloxane polymer 3.
[0048] Examples 1-5
[0049] The specific proportions of the components in Examples 1-5 are shown in Table 2
[0050] Table 2
[0051]
[0052] According to Table 2, a method for preparing a fouling-release marine antifouling coating having a soft-hard segment coordinated topological structure and a cured coating thereof according to Examples 1-5 is as shown in the following steps:
[0053] (1) adding the soft and hard segment synergistic modified polysiloxane polymer and the auxiliary agent in a dispersing and stirring device in sequence, and then dispersing at 100 rpm for 20 minutes, then adding the pigment and filler and the first solvent to the dispersing and stirring device, and continuing to disperse at the same speed for 20 minutes, that is, preparing a fouling-release marine antifouling coating with a soft and hard segment synergistic topological structure, and then sealing and storing;
[0054] (2) The coating is applied by spraying, rolling, brushing, etc., and cured for at least 48 hours to prepare a coating with a film thickness of 150 to 250 μm.
[0055] In actual application, the antifouling coating can be prepared by conventional methods of marine antifouling coatings, and is not limited to the above preparation method.
[0056] Comparative Example 1 (Ordinary silicone low surface energy marine antifouling coating)
[0057] The common organosilicon low surface energy marine antifouling paint comprises the following raw materials in parts by weight: 90.0 parts of polysiloxane resin, 30.0 parts of pigments and fillers, 4.0 parts of cross-linking curing agent, 1.5 parts of catalyst, 0.5 parts of auxiliary agent and 10.0 parts of third solvent.
[0058] The polysiloxane resin is α, ω-dihydroxy polydimethylsiloxane with a viscosity of 10000 mPa·s; the pigment is zinc oxide; the cross-linking curing agent is tetraethyl orthosilicate; the catalyst is dibutyltin disilicate; the auxiliary agent is 0.5 parts of BYK161 dispersant from BYK; and the third solvent is xylene.
[0059] (1) 90.0 parts of α,ω-dihydroxy polydimethylsiloxane with a viscosity of 10000 mPa·s and 30.0 parts of micron-sized zinc oxide were added to a disperser and dispersed at 300 rpm for 30 min. Subsequently, 0.5 parts of BYK161 dispersant from BYK was added to the disperser at 200 rpm and dispersed for 30 min. The mixture was then ground with a sand mill to a fineness of less than 40 μm to prepare a pre-dispersed slurry and canned for standby use.
[0060] (2) 4.0 parts of tetraethyl orthosilicate and 10.0 parts of xylene were mixed evenly to prepare a crosslinking curing agent component, which was then canned for standby use; 1.5 parts of dibutyltin dioxysilicate and 20.0 parts of xylene were mixed evenly to prepare a catalyst component, which was then canned for standby use;
[0061] (3) Before use, the pre-dispersed slurry, the cross-linking curing agent component, and the catalyst component are stirred uniformly according to the ratio. After the obtained coating is applied and cured, a common organic silicon low surface energy marine antifouling coating with a thickness of 150 to 250 μm is obtained.
[0062] Comparative Example 2
[0063] Compared with Example 1, no anionic monomer is introduced into the prepared modified polysiloxane polymer, the remaining components and their weight parts are the same, and the preparation process is also the same as that of Example 1.
[0064] <Specific test experiments and conditions>
[0065] Test 1: Surface Free Energy
[0066] The contact angles of deionized water and diiodomethane on the surface of the cured coating were measured using the XG-CAMC3 fully automatic contact angle meter produced by Shanghai Xuanzhun Instrument Co., Ltd. Before the measurement, the coating surface needs to be cleaned with anhydrous ethanol and dried, and then the surface free energy of the coating is calculated according to the Owens two-liquid method.
[0067] Test 2: Pull-off method to measure adhesion after 100 days of seawater immersion (steel plate, epoxy intermediate paint)
[0068] The BGD500 digital semi-automatic adhesion tester produced by Guangzhou Biaogeda Precision Instrument Co., Ltd. was used to measure the adhesion of the coating applied on the corresponding substrate or epoxy intermediate paint. The steel plate needs to be polished with 800-grit sandpaper before use, and the epoxy intermediate paint used is the epoxy micaceous iron intermediate paint produced by Shanghai Jinsi Di. Before the test, it needs to be immersed in sterilized seawater for 100 days, and then taken out and dried for testing.
[0069] Test 3: Antifouling performance
[0070] A suspension containing at least 108 units of Streptococcus salivarius was dispersed in 20 ml of tryptic soy broth and incubated at 38°C, 5% CO2 for 2 hours. The suspension was then further diluted and inoculated in agar supplemented with 5% sheep blood and incubated at 38°C, 5% CO2 for 48 hours, and then the units containing six colonies were dispersed in 10 ml of tryptic soy broth. Subsequently, 20 ml of the above bacterial suspension was covered on the coating of 10×5 cm area and incubated at 38°C, 5% CO2 for 24 hours. After the incubation, each sample needed to be rotated and rinsed in 45 ml of distilled water for 30 seconds, and then rinsed with 50 ml of distilled water to remove non-sticky materials. The surface-adherent bacteria were observed using a Simga300 scanning electron microscope produced by Carl Zeiss, Germany.
[0071] The specific test results of Examples 1-5 and Comparative Examples 1-2 are shown in Table 3.
[0072] Table 3
[0073]
[0074] As can be seen from Table 3, compared with Comparative Example 2, Examples 1-5 have lower surface free energy, which can ensure that fouling organisms are difficult to adhere to the coating surface, thus having good antifouling performance; at the same time, the adhesion of Examples 1-5 on steel plates and epoxy intermediate paints is better than that of Comparative Example 1, which can effectively improve the disadvantage of poor adhesion between the coating and the substrate, and can be firmly bonded to various substrates and intermediate paints. The above tests can confirm that compared with the comparative examples, the embodiments have excellent antifouling effects while having good adhesion. Therefore, the coating of the present invention is applied to the antifouling of marine facilities, especially various marine facilities that are immersed in seawater environments for a long time, which can effectively inhibit the adhesion of fouling organisms on the coating surface, and it is not easy to peel off after long-term use.
[0075] The above is a description of the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A fouling-release marine antifouling coating with a soft and hard segment coordinated topological structure, characterized in that: In parts by weight, it includes: The structure of the soft and hard segment cooperatively modified polysiloxane polymer is that the main chain is hydrophobic methylsiloxane, and the two ends are hard segment molecular segments from anionic monomers and hydrophilic amide monomers.
2. The fouling-releasing marine antifouling coating with a soft-hard segment coordinated topological structure according to claim 1, characterized in that: The soft and hard segment synergistically modified polysiloxane polymer is prepared by the following steps: (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, an anionic monomer, a hydrophilic amide monomer, a carboxyl polysiloxane and a second solvent are added in sequence, and then the pH is adjusted to be greater than 10 with a sodium hydroxide / ethanol mixed solution, and the reaction is stirred at 20 to 100 rpm at 40 to 50° C. for 10 to 20 hours; (2) filtering the precipitated product after the reaction, washing it with deionized water for at least three times, and then drying it in a vacuum device to obtain a soft-hard segment synergistically modified polysiloxane polymer.
3. The fouling-releasing marine antifouling coating with a soft-hard segment coordinated topological structure according to claim 2, characterized in that: The weight ratio of the anionic monomer, the hydrophilic amide monomer, the carboxyl polysiloxane and the solvent is (3-8): (5-10): (50-80): (100-150).
4. The fouling-releasing marine antifouling coating with a soft-hard segment coordinated topological structure according to claim 2, characterized in that: The anionic monomer is selected from one of sodium 2-carboxyethyl acrylate, sodium acrylate, sodium indoleacrylate and sodium alginate.
5. The fouling-releasing marine antifouling coating with a soft-hard segment coordinated topological structure according to claim 2, characterized in that: The hydrophilic amide monomer is selected from one of N-(2-hydroxyethyl) acrylamide, methacrylamide and dimethylaminopropyl acrylamide.
6. The fouling-releasing marine antifouling coating with a soft-hard segment coordinated topological structure according to claim 2, characterized in that: The carboxyl polysiloxane is selected from dicarboxyl-terminated polysiloxane, and has a viscosity of 2000-5000 mPa·s at room temperature.
7. The fouling-releasing marine antifouling coating with a soft-hard segment coordinated topological structure according to claim 2, characterized in that: The second solvent is selected from one of ethanol, acetone and toluene.
8. The fouling-releasing marine antifouling coating with a soft-hard segment coordinated topological structure according to claim 1, characterized in that: The auxiliary agent is selected from at least one of a wetting and dispersing agent, a defoaming agent and a leveling agent.
9. The fouling-releasing marine antifouling coating with a soft-hard segment coordinated topological structure according to claim 1, characterized in that: The first solvent is selected from one of methanol, xylene and acetone.
10. A method for preparing the fouling-release marine antifouling coating with a soft-hard segment coordinated topological structure according to claim 1, characterized in that: The following steps are involved: (1) In a reaction device protected by nitrogen and equipped with a stirring reflux device, an anionic monomer, a hydrophilic amide monomer, a carboxyl polysiloxane and a second solvent are added in sequence, and then the pH is adjusted to be greater than 10 with a sodium hydroxide / ethanol mixed solution, and the reaction is stirred at 20 to 100 rpm at 40 to 50° C. for 10 to 20 hours; (2) filtering the precipitated product after the reaction, washing it with deionized water for at least three times, and then drying it in a vacuum device to obtain a soft and hard segment synergistically modified polysiloxane polymer; (3) Add the soft and hard segment synergistic modified polysiloxane polymer and the additive obtained in step 2 to the dispersing and stirring equipment in sequence, stir and disperse, then add the pigment, filler and the first solvent to the dispersing and stirring equipment and continue to stir and disperse, so as to obtain the fouling-release marine antifouling coating with a soft and hard segment synergistic topological structure, and then seal and store.
Citation Information
Patent Citations
Macroinitiator containing hydrophobic segment
CN103502317A
Catechol functional modified fouling release type marine antifouling paint
CN118652627A
Hair composition comprising a polysaccharide grafted with a polysiloxane, and a fixing polymer
US20020197225A1
